Propolis effects on blood sugar and lipid metabolism, inflammatory indicators, and oxidative stress in people with type 2 diabetes: a systematic review and meta-analysis - Zhang, Yihua; Ding, Shuo; Li, Wenjing; Wang, Xiumei; Lv, Jie; Niu, Qingmei; Zhang, Qian (Frontiers in Nutrition, 2025)
BackgroundType 2 Diabetes Mellitus (T2DM) poses a significant global health challenge. Propolis, a natural bioactive compound, is proposed to modulate glucose and lipid metabolism and exert anti-inflammatory effects. However, previous reviews have limited scope, and the effects of propolis on T2DM remain debated, particularly concerning lipid profiles, glycemic control, inflammation, and oxidative stress.MethodsA systematic search was conducted across Chinese National Knowledge Infrastructure (CNKI), VIP, SinoMed, Wanfang Data, PubMed, Cochrane Library, Embase, Scopus, and Web of Science, with the search time limit set from the establishment of the databases to 20 May 2025. Study quality was assessed using the Cochrane Risk of Bias Assessment Tool version 2 (ROB 2); evidence quality was evaluated via the Grading of Recommendations, Assessment, Development, and Evaluation (GRADE) approach; and meta-analysis was performed using RevMan 5.4.ResultsIn total, 12 randomized controlled trials (RCTs) with 731 participants were included in this study. Propolis supplementation significantly increased high-density lipoprotein cholesterol (HDL-C) levels (mean difference (MD) = 0.13, 95% CI 0.10–0.16, p < 0.00001), and reduced low-density lipoprotein cholesterol (LDL-C) (MD = −0.32, 95% CI: −0.56 to −0.08; p = 0.009) and triglyceride (TG) levels (MD = −0.15, 95% CI: −0.30 to −0.01; p = 0.04). It also improved glycemic control, lowering fasting blood sugar (FBS) (MD = −1.13, 95% CI: −2.00 to −0.27, p = 0.01), homeostasis model assessment of insulin resistance (HOMA-IR) (MD = −0.95, 95% CI: −1.36 to −0.55, p < 0.00001), and glycosylated hemoglobin (HbA1c) (MD = −0.44, 95% CI: −0.78 to −0.11, p = 0.01). Furthermore, propolis significantly reduced C-reactive protein (CRP) (MD = −2.68, 95% CI: −3.48 to −1.89, p < 0.00001). However, no significant effects were observed for total cholesterol (TC), tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), superoxide dismutase (SOD), or malondialdehyde (MDA).ConclusionPropolis may improve lipid and glucose profiles and reduce inflammation in T2DM. While current evidence does not confirm significant effects on oxidative stress markers, considering the limitations of existing clinical studies and positive basic research findings, its potential antioxidant effects require validation through high-quality RCTs.Systematic review resistrationThis study was registered with PROSPERO (registration number: CRD42024577722) https://www.crd.york.ac.uk/PROSPERO/#loginpage.